Reviewing the recording quality of a local string instrument (sape) from the perspective of sound preservation - Musib, Ahmad Faudzi (Universiti Pendidikan Sultan Idris, 2016)
Although technologies have rapidly advanced in the modern world, musicians and music scholars rarely understand new technologies and hence cannot comprehend the impact of recording technologies on their careers. Recordings of ethnic instruments that are available in the marketplace today show various types of timbre determined by different sampling rates, choice of microphone placements and acoustic environment. In many cases, the timbre produced in recordings of one ethnic instrument called sape is highly diversified. Music recordings available for ethnic instruments such as the sape of the Orang Ulu, Kenyah and other ethnic groups were manipulated either through the sound of the instrument itself or through the original recording that was extracted from various recording mediums, or recorded in a “mock-up” context created by producers. The effects of all these manipulations have misled listeners into thinking that what they are hearing are the original sounds of instruments such as sape. This situation is similar to a live performance. Many audience members are unaware that the final acoustic outcome for the audience is not only the sound produced by the instrument but also through the main speaker monitors of a performance venue. Local folk music instruments such as sape are traditionally played in a rural and/or communal setting with its unique sound environment. This contextual sound environment however tends to be ignored in the sound reinforcement of live performances as well as in audio recordings. All of the above affects the quality of audio recordings. The intention of this article is to compare, analyse and review the quality of audio recordings of sape from various perspectives, including wave analysis and audio signal audibility. This article suggests for a more advanced sound preservation approach through a constructed scheme for recordings.